Пластмассовые зубчатые колеса: методика и программа автоматизированного расчета корректировок размеров формообразующих зубчатых матриц - Старжинский, В. Е.; Гоман, Аркадий Михайлович; Ишин, Николай Николаевич (НТУ "ХПИ", 2008)
Procedure, algorithm and results of automation design of controlled dimension updates of molded plastic gears are considered taking into account the datareceived at measuring pilot batch of gear work-pieces. The possibility of integral increasing probability of corresponding dimensional inaccuracies of gears manufactured in the improved mold dies to accuracy indices indicated in technical documentation is demonstrated.
Keywords: метод эвольвента; ролики; диаметр вершин; шаг зацепления; толщина зуба